2021
DOI: 10.1590/1809-4392202004731
|View full text |Cite
|
Sign up to set email alerts
|

Using osteological measurements to estimate body length in Amazonian manatees

Abstract: Body length is an important parameter in morphological, ecological and behavioral studies of a species and contributes to the understanding of the body condition of individuals. This parameter is essential for conservation and management strategies by informing studies evaluating growth rates, physical maturity and classification of individuals into age groups, promoting better accuracy for the biological parameters of the species. The aim of this study was to identify predictors of body length for Amazonian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The Amazonian manatee is the smallest living sirenian, reaching up to 2.75 m in length and weighing up to 420 kg (Amaral et al, 2010a). The range of body length and weight at birth was estimated as 85 -105 cm and 10 -18 kg, respectively (Best, 1984;Amaral et al, 2010a) and there are no differences in body size or even in cranial characters between the sexes (Domning & Hayek, 1986;Amaral et al, 2010a;Valdevino, 2016;Barros et al, 2017;Valdevino et al, 2021). Growth curves were estimated for captive (Colares, 2002;Albuquerque Junior, 2003) and freeranging individuals (Vergara- Parente et al, 2010), and the growth rates observed, despite methodological differences among studies, were less than 0.4 cm/year.…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…The Amazonian manatee is the smallest living sirenian, reaching up to 2.75 m in length and weighing up to 420 kg (Amaral et al, 2010a). The range of body length and weight at birth was estimated as 85 -105 cm and 10 -18 kg, respectively (Best, 1984;Amaral et al, 2010a) and there are no differences in body size or even in cranial characters between the sexes (Domning & Hayek, 1986;Amaral et al, 2010a;Valdevino, 2016;Barros et al, 2017;Valdevino et al, 2021). Growth curves were estimated for captive (Colares, 2002;Albuquerque Junior, 2003) and freeranging individuals (Vergara- Parente et al, 2010), and the growth rates observed, despite methodological differences among studies, were less than 0.4 cm/year.…”
Section: Morphologymentioning
confidence: 99%
“…Growth curves were estimated for captive (Colares, 2002;Albuquerque Junior, 2003) and freeranging individuals (Vergara- Parente et al, 2010), and the growth rates observed, despite methodological differences among studies, were less than 0.4 cm/year. An allometric pattern of growth is observed in the skull and other bones (Domning & Hayek, 1986;Valdevino, 2016;Barros et al, 2017;Valdevino et al, 2021). Therefore, osteological measurements can be used on body length estimations for this species (Valdevino et al, 2021).…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation